2023
DOI: 10.3390/antibiotics12030521
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Strategies for Preventing Healthcare-Associated Infections across the Surgical Pathway: An Italian Multisociety Document

Abstract: Healthcare-associated infections (HAIs) result in significant patient morbidity and can prolong the duration of the hospital stay, causing high supplementary costs in addition to those already sustained due to the patient’s underlying disease. Moreover, bacteria are becoming increasingly resistant to antibiotics, making HAI prevention even more important nowadays. The public health consequences of antimicrobial resistance should be constrained by prevention and control actions, which must be a priority for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
2
0
1
Order By: Relevance
“…Various implementation interventions have been described and can potentially be used to promote compliance with guidelines [75]. In the setting of SSI prevention, in 2019, Ariyo et al published a systematic review of utilised implementation strategies [76].…”
Section: Discussionmentioning
confidence: 99%
“…Various implementation interventions have been described and can potentially be used to promote compliance with guidelines [75]. In the setting of SSI prevention, in 2019, Ariyo et al published a systematic review of utilised implementation strategies [76].…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that experience may influence certain aspects of hygienic practice, indicating a potential area for targeted training and development among less experienced anesthetists 15 . Due to the self-reported nature of the survey and the voluntary nature of the participation, this study contains the potential for response and non-response bias [16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, resistencia bacteriana frente a desinfectantes es un problema frecuente, en varias ocasiones se relacionan con Infecciones asociadas a la Atención en Salud (IAAS) (6). El uso de desinfectantes de grado hospitalario ayuda a evitar estas infecciones garantizando esterilidad y limpieza de estas áreas; sin embargo, actualmente las infecciones nosocomiales han incrementado en gran medida (7). Se puede observar en los últimos años la aparición de resistencias ligada a biosidas, particularmente a desinfectantes de uso hospitalario, siendo este un punto un factor favorable en la supervivencia y multirresistencia dando como resultado contaminación intrahospitalaria (8).…”
Section: Introductionunclassified